Preparation method of nitrogen-carbon-doped phosphating bimetal MOF (Metal Organic Framework) derivative composite catalyst
Through nitrogen-carbon-doped phosphated bimetallic MOF-derived composite catalyst, the problem of insufficient stability and activity of precious metal catalysts in electrolytic hydrogen production is solved, and efficient electrolytic hydrogen production within the entire pH range is achieved, reducing costs and improving stability.
Patent Information
- Application Number
- CN202510571948.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-07-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrolytic hydrogen production technology lacks low-cost, high-stability and suitable for the full pH range of bimetallic catalysts. In particular, noble metal catalysts are easily oxidized and dissolved in alkaline environments, and have poor stability, and the existing non-precious metal catalysts are insufficiently active under different pH conditions.
A phosphated bimetallic MOF-derived composite catalyst is used to adopt a nitrogen-carbon-doped phosphated bimetallic MOF-derived composite catalyst. Through bimetallic synergistic effect, nitrogen/phosphorus co-doped carbon matrix and multi-stage pore structure design, combined with a low-temperature phosphating process, Ni-Co-based catalyst is prepared to form a CoP@NiP core-shell structure to enhance catalytic activity and stability.
It realizes efficient electrolysis of hydrogen production in the entire pH range, with lower catalyst cost than traditional precious metals and better stability than existing technology, and is suitable for large-scale industrial applications.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen production by electrolyzing water, and particularly relates to a preparation method of a highly efficient composite catalyst based on a bimetallic MOF (metal-organic framework) precursor, nitrogen-carbon doping and phosphating process, which is applicable to hydrogen production by electrolyzing water under all pH conditions. Background Art
[0002] The energy problem has always been the biggest difficulty and challenge faced by humans currently. Therefore, the development and application of new energy are effective ways to reduce the consumption of fossil energy and solve environmental pollution. Hydrogen energy is a clean energy with a high calorific value, and the water generated by the combustion of hydrogen and oxygen can be reused repeatedly, enabling zero pollution. As a clean and renewable energy source, hydrogen has a high combustion calorific value and is thus considered an ideal carrier for building the future clean energy pattern. The electrolysis of water is considered one of the effective ways to obtain high-purity hydrogen. Selecting a suitable catalyst can effectively reduce the overpotentials of the two half-reactions of electrolyzing water: hydrogen evolution reaction (HER) at the cathode and oxygen evolution reaction (OER) at the anode, thereby reducing the energy consumption of the whole reaction.
[0003] Transition metal phosphides exhibit excellent electrocatalytic performance in hydrogen production by electrolyzing water due to their hydrogenase-like HER catalytic mechanism and unique structure. Moreover, they are considered promising HER electrocatalytic materials because of their rich reserves and low prices. At the same time, it has also been proven that they can catalyze OER, which provides the possibility for designing high-performance overall water electrolysis catalysts. Metal-organic frameworks (MOFs) are a kind of coordination polymers that have developed rapidly in recent years. They can combine the advantages of inorganic and organic substances. On the one hand, they have high structural modifiability, that is, catalytically active transition metal sites can be exposed through design, and the microenvironment of metal nodes can be regulated by designing ligands to improve their catalytic activity; on the other hand, they have the advantages of an ordered porous crystal structure, a large specific surface area, and a large porosity, which can increase the contact area with reactants and help charge transfer and mass transfer during the catalytic process. The HER electrocatalyst in the existing electrolytic cell device is Pt / C. Although commercial Pt / C has high HER activity, its scarcity and high cost (about 30,000 / kg) severely restrict large-scale applications. Moreover, it also needs to be used in combination with IrO2. As the mainstream OER catalyst, IrO2 has an even higher price (about 150,000 / kg), and noble metal catalysts are prone to oxidation and dissolution in an alkaline environment, with poor stability (decay > 20% within 100 hours). Among many non-noble metal catalysts, catalysts of transition metals such as Ni and Co have great commercial potential due to their good catalytic activity. Adding graphene can improve the conductivity of the material, and adding N atoms and utilizing the synergistic effect of Ni and Co can improve their performance.
[0004] The prior art lacks a bimetallic catalyst with low cost, high stability and applicable to the full pH range (acidic, neutral, alkaline). The above problems need to be solved through structural design (hierarchical pores, core-shell), element doping (N / P) and process optimization (low-temperature phosphidation). Therefore, it is of great significance to prepare a nitrogen and carbon-doped phosphided bimetallic MOF-derived composite catalyst. The present invention solves the above technical bottlenecks through the bimetallic synergistic effect, nitrogen / phosphorus co-doped carbon matrix and hierarchical pore structure design. Summary of the Invention
[0005] The object of the present invention is to provide a preparation method of a nitrogen and carbon-doped phosphided bimetallic MOF-derived composite catalyst with low cost, high activity and applicable to overall pH electrolytic water hydrogen production.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation method of a nitrogen and carbon-doped phosphided bimetallic MOF-derived composite catalyst, comprising the following steps: Step 1: Dissolve Ni(NO3)2·6H2O and Co(NO3)2·6H2O in methanol, and stir to form a metal salt solution. Dissolve 2-methylimidazole in methanol, quickly pour it into the metal salt solution, stir and transfer it to a high-pressure reaction kettle, and react at 120 °C for 24 hours. Centrifuge, wash and dry to obtain a bimetallic MOF precursor NiCo-MOF; Step 2: Perform high-temperature pyrolysis in an inert atmosphere (Ar / N2), control the temperature at 700-900 °C, the heating rate at 2-5 °C / min, and keep the temperature for 2-4 hours; Step 3: Introduce SiO2 nanosphere template as a hard template, remove the template by HF acid etching after carbonization to form a mesoporous-macroporous hierarchical structure; Step 4: Place the carbonized material and the phosphorus source sodium hypophosphite (NaH2PO2) at the upstream and downstream of a tube furnace respectively, heat up to 300-400 °C at a rate of 2 °C / min under an Ar atmosphere, and keep the temperature for 2-4 hours to form a CoP@NiP / NC composite structure.
[0007] Step 5: Purify and wash with 0.5 M HCl or HNO3 acid for 1-2 hours to remove unreacted metal oxides, with a usage amount 10-20 times that of the catalyst, then use carbon cloth or nickel foam as a substrate, with a loading amount of 1-3 mg / cm² and an impregnation time of 12-24 hours, and a drying temperature of 80-150 °C.
[0008] Preferably, in the raw materials of the nitrogen and carbon-doped phosphided bimetallic MOF-derived composite catalyst, transition metals (Ni, Co) are used to replace noble metals (Pt, Ru), and the cost is only 1 / 10 of that of traditional catalysts.
[0009] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, MOF is used as a precursor, and a second metal (such as Ni, Co) is introduced by a solvothermal method or a coprecipitation method, and the metal ratio is precisely controlled.
[0010] Furthermore, the bimetallic synergistic effect: the Ni-Co atomic ratio (1:1 - 3:1) regulates the electronic structure, Ni promotes H adsorption, and Co accelerates OH - desorption, synergistically reducing the overall hydrolysis voltage to 1.68 V (vs. RHE).
[0011] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, the carbonization temperature is usually 700 - 900 °C, and it is calcined in an inert atmosphere (N2 or Ar). The carbon layer thickness can be controlled by a programmed heating method.
[0012] Furthermore, pre-carbonization at 700 °C (2 °C / min) forms a carbon skeleton, and high-temperature treatment at 900 °C (5 °C / min) promotes the dispersion of metal particles (particle size ~5 nm).
[0013] Furthermore, the N-doped carbon (N content ~8 at%) generated by the pyrolysis of 2-methylimidazole can provide an electron-rich environment, reduce the H⁺ adsorption energy (ΔGH*≈0.12 eV), and at the same time enhance electron transport (electrical conductivity >200 S / m).
[0014] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, MOF as a precursor can directly generate a composite catalyst through steps such as pyrolysis and phosphidation, avoiding the complex loading and modification processes in traditional methods.
[0015] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, by adjusting the metal ratio or doping elements (such as N, P) of MOF, the active centers of the catalyst can be designed directionally.
[0016] Furthermore, the NiP shell protects the CoP core from corrosion, extending the stability in an acidic environment to 1000 hours (current retention rate >95%).
[0017] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, phosphidation treatment (NiP, CoP) improves the chemical stability of the metal and reduces the overpotential of the hydrogen evolution / oxygen evolution reaction.
[0018] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, the low-temperature phosphidation technology combined with sodium hypophosphite as a phosphorus source can achieve the uniform dispersion of metal phosphides.
[0019] Furthermore, hypophosphite low-temperature phosphidation (300 - 400 °C) converts Ni / Co oxides into NiP / CoP, optimizing the d-band center position of the metal (the d-band center of CoP shifts upward by 0.3 eV), and enhancing the hydrolysis dissociation efficiency.
[0020] Preferably, in the preparation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst, hydrofluoric acid etching is used to construct a hollow structure.
[0021] Furthermore, the template method optimizes the pore structure. After the SiO2 template is etched, a hierarchical structure of mesopores (2 - 50 nm) and macropores (>50 nm) is formed, with a specific surface area of 520 m² / g and a 40% increase in mass transfer efficiency.
[0022] Furthermore, fluorination in an Ar / HF mixed atmosphere generates a CoF3 / NiF2 dispersed phase, enhancing the surface polarity and improving the OER activity in an alkaline environment (the overpotential is only 238 mV@10 mA / cm²).
[0023] The nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst has achieved multiple breakthroughs in catalytic activity, stability, and economy through structural design, component synergy, and process innovation. Its advantages are not only reflected in superior performance compared to traditional single-metal or non-doped materials but also provide the possibility for large-scale industrial applications, especially in the field of clean energy (such as hydrogen production by electrolysis of water). The nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst combines bimetallic MOF with a nitrogen / phosphorus co-doped carbon matrix to solve the problems of poor conductivity and insufficient active sites of traditional catalysts.
[0024] In the solution, the structural innovation of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst: Design of the bimetallic MOF precursor: Ni-Co bimetallic MOF is used as the precursor, and the d-band center of the active site is optimized through the electron synergy effect between metals, enhancing the catalytic activity.
[0025] Nitrogen / phosphorus co-doped carbon matrix: A nitrogen-doped carbon framework is formed by pyrolyzing the MOF organic ligand (such as 2-methylimidazole), and phosphorus elements are introduced through phosphidation treatment to form a conductive network and defect sites, enhancing the charge transfer efficiency.
[0026] Hierarchical pore structure and core-shell morphology: A hierarchical or porous structure is constructed through the template method (polystyrene), and impurities are removed by pickling to maximize the exposure of active sites and promote mass transfer.
[0027] In the solution, the preparation process of the nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst is optimized: In-situ Phosphidation Process: Low-temperature gas-solid phase phosphidation using sodium hypophosphite (NaH2PO2) to convert metal oxides into metal phosphides, avoiding carbon structure collapse caused by high temperatures.
[0028] Stepwise Pyrolysis and Fluorination Treatment: Stepwise heating (700 - 900 °C) in an inert atmosphere to achieve carbonization and dispersion of metal particles, followed by fluorination treatment to form a metal fluoride dispersed phase and enhance surface polarity. Detailed Implementation Modes
[0029] To better explain the present invention, exemplary embodiments of the present invention will be described in more detail below. Although the following shows exemplary embodiments of the present invention, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to convey the scope of the present invention completely to those skilled in the art. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0030] The following are the specific implementation schemes of the nitrogen and carbon-doped phosphided bimetallic MOF-derived composite catalyst. Combining the bimetallic synergistic effect, nitrogen / carbon doping optimization, structure optimization / phosphidation process, and post-treatment process, it will be described in detail step by step: 1. Synthesis of Bimetallic MOF Precursors: Select cobalt (Co(NO3)2·6H2O) and nickel (Ni(NO3)2·9H2O) and mix them in a molar ratio of 1:1 to 3:1, and control the total metal ion concentration at 0.05 - 0.2 mol / L.
[0031] Use 2-methylimidazole (C4H6N2) with a high nitrogen content (~33%), and the molar ratio of 2-methylimidazole to metal salt is 4:1.
[0032] Solvent: Methanol or deionized water, with a volume 1.5 - 2 times the sum of the metal salt solution and the ligand solution.
[0033] Reaction time: 24 hours, temperature: 120 °C.
[0034] 2. Construction of Nitrogen-Doped Carbon Matrix Carbonization process temperature: 700 - 900 °C, heating rate: 2 - 5 °C / min, holding time: 2 - 4 hours.
[0035] Protective gas: Argon or nitrogen, flow rate: 50 - 100 mL / min.
[0036] 3. Optimization of Pore Structure by Template Method Mass ratio of template agent SiO2 to MOF precursor: 1:10.
[0037] Etching conditions: hydrofluoric acid (concentration 5 - 10%), etching time: 12 hours.
[0038] 4. Phosphating treatment The mass ratio of sodium hypophosphite (NaH2PO2) to the carbonized product: 1:10 - 1:20, placed separately at the upstream and downstream of the tube furnace.
[0039] Temperature: 300 - 400 °C, time: 2 - 4 hours.
[0040] Protective gas: argon, flow rate: 50 mL / min.
[0041] 5. Post-treatment and performance optimization Pickling and purification: pickling solution: 0.5 M HCl or HNO3, dosage is 10 - 20 times that of the catalyst.
[0042] Washing time: 1 - 2 hours, to remove unreacted metal oxides.
[0043] Loading on the conductive substrate: substrate (carbon cloth or nickel foam) loading amount: 1 - 3 mg / cm².
[0044] Impregnation time: 12 - 24 hours, drying temperature: 80 - 150 °C.
[0045] Through the above steps, a high-performance nitrogen and carbon co-doped phosphated bimetallic MOF-derived composite catalyst can be prepared on a large scale. The cost of this catalyst is much lower than that of the commercially available Pt / C catalyst at present stage, and it can be mass-produced through a continuous tube furnace (production capacity > 100 kg / day), and the annual global output of the raw materials (Ni, Co salts) exceeds 100,000 tons, with a stable supply chain.
[0046] Characterization data: Structure characterization: X-ray diffraction (XRD): Precursor stage: characteristic peaks of bimetallic MOF (NiCo-MOF) are located at 2θ = 10.2° and 12.5°.
[0047] After carbonization: the (002) crystal plane peak of graphite carbon appears (2θ ≈ 26°).
[0048] After phosphating: crystal phases of CoP and NiP are generated, without impurity peaks.
[0049] Transmission electron microscopy (TEM): Core-shell structure: the CoP@NiP core-shell structure is clearly visible, and the shell thickness is about 2 nm.
[0050] Metal dispersion: NiP / CoP particles are evenly dispersed in the nitrogen-doped carbon matrix, with an average particle size of 5 ± 1 nm.
[0051] X-ray Photoelectron Spectroscopy (XPS): N 1s spectrum: Coexistence of pyridine nitrogen (398.5 eV) and graphitic nitrogen (401.2 eV), with a total nitrogen content of approximately 8 at%.
[0052] P 2p spectrum: The metal-P bond (129.8 eV) confirms successful phosphidation.
[0053] Co 2p and Ni 2p spectra: The characteristic peaks of metal phosphides (such as the Co²⁺ peak position in CoP) are significantly different from the oxidation states.
[0054] Specific Surface Area and Pore Structure (BET): Specific surface area: 520 m² / g (mesopores 2 - 50 nm, macropores > 50 nm).
[0055] Pore volume: 0.89 cm³ / g, with mesopores accounting for 70% and macropores accounting for 25%.
[0056] Performance Testing: LSV curve: In 1 M KOH, the HER current density of CoP@NiP / NC at 10 mA / cm² corresponds to an overpotential of 141 mV and a Tafel slope of 42 mV / dec.
[0057] EIS spectrum: The charge transfer resistance (Rct) is only 12 Ω, significantly lower than that of commercial Pt / C (25 Ω).
[0058] Acid Corrosion Test: After soaking in 0.5 M H2SO4, XRD shows no metal oxide peaks, indicating that the core-shell structure effectively inhibits corrosion.
[0059] Economic Analysis Table The catalyst of the present invention has a stability > 1000 hours (current retention rate > 95%) in an acidic environment, far exceeding that of commercial Pt / C (100 hours). Examples
[0060] Example 1: Ni / Co molar ratio of 1:1, carbonization temperature of 800 °C, and phosphidation temperature of 350 °C. Specific operation steps for change: Step 1: Synthesize Ni1Co1-MOF with Ni(NO3)2·6H2O and Co(NO3)2·6H2O in a 1:1 molar ratio.
[0061] Step 2: Pyrolyze at 800 °C with a heating rate of 2 °C / min.
[0062] Step 4: Phosphidate at 350 °C to generate Co1P@Ni1P / NC.
[0063] Example 2: The molar ratio of Ni / Co is 3:1, the carbonization temperature is 900 °C, and the phosphidation temperature is 400 °C. Specific operation steps for changes: Step 1: Synthesize Ni3Co1-MOF with Ni / Co = 3:1.
[0064] Step 2: Pyrolyze at 900 °C with a heating rate of 5 °C / min.
[0065] Step 4: Phosphidate at 400 °C to generate Co1P@Ni3P / NC.
[0066] Comparative example: A single-metal Ni-MOF-derived catalyst. Specific operation steps for changes: Synthesize Ni-MOF using only Ni salt.
[0067] Except for changing the above conditions, the other conditions are the same as the specific implementation of the nitrogen-carbon-doped phosphidated bimetallic MOF-derived composite catalyst.
[0068] Comparison table of performance indicators of the composite catalyst (CoP@NiP / NC) of the present invention and three examples Example 1: The molar ratio of Ni / Co is 1:1, the carbonization temperature is 800 °C, and the phosphidation temperature is 350 °C. HER overpotential is 141 mV@10 mA / cm², and the overall water splitting voltage is 1.68 V.
[0069] Example 2: The molar ratio of Ni / Co is 3:1, the carbonization temperature is 900 °C, and the phosphidation temperature is 400 °C. OER overpotential is 238 mV@10 mA / cm², and the stability in alkaline environment is >90%@100 hours.
[0070] Comparative example: A single-metal Ni-MOF-derived catalyst, with an overall water splitting voltage as high as 1.82 V, significantly higher than 1.68 V of the catalyst of the present invention, proving that the synergy of the bimetal (Ni-Co) is crucial for reducing the water splitting voltage.
[0071] Phosphidation temperature: In Example 2 at a higher phosphidation temperature (400 °C), the HER overpotential in acidic environment drops to 116 mV, better than 141 mV in Example 1 (alkaline environment), indicating that temperature regulation can optimize the dispersion of active sites.
[0072] Ni / Co ratio: When Ni / Co = 3:1 (Example 2), the overall water splitting voltage drops to 1.54 V in acidic environment, better than 1.68 V at a ratio of 1:1 (alkaline), indicating that the metal ratio can be flexibly adapted to different application scenarios.
[0073] Comparison table of the cross-pH performance of this catalyst The catalyst of the present invention exhibits excellent performance under acidic, neutral, and alkaline conditions (overall hydrolysis voltage ≤ 1.75 V), while comparative examples such as commercial Pt / C require the combination of IrO2, and single-metal Ni-MOF is only applicable to alkaline environments.
[0074] Analysis of the mechanism of cross-pH adaptability: Acidic environment: Dependent on the direct reduction of H⁺, the conductivity of the catalyst and the H adsorption energy are crucial. The nitrogen-doped carbon matrix reduces the H adsorption energy through electronic structure regulation, and a protective layer is formed on the surface of the phosphide to prevent acid corrosion.
[0075] Neutral environment: It is necessary to overcome the low ionic conductivity, and the hierarchical pore (micro-meso-macropore) structure is used to accelerate the transport of H2O and ions, such as the MOF-derived three-dimensional porous carbon matrix.
[0076] Alkaline environment: It is necessary to promote the dissociation of H2O into H⁺ and OH⁻. The bimetal optimizes the water dissociation step through synergistic effects, and the nitrogen-doped carbon layer provides a highly conductive network.
[0077] Comparison table of key performance of this catalyst and other catalysts for hydrogen production by electrolyzing water From the above data, it can be seen that the electrochemical activity and stability of this catalyst are relatively excellent compared with the current catalysts for hydrogen production by electrolyzing water.
[0078] This catalyst comprehensively surpasses the existing technologies in terms of activity (alkaline HER overpotential 141 mV), stability (acidic > 1000 hours), and economy (cost 500 $ / kg) through the strategies of bimetal synergy, hierarchical pore structure, and heteroatom doping. It is suitable for the whole pH hydrogen production by electrolyzing water scenario and is an ideal choice to replace noble metal catalysts.
[0079] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention.
Claims
1. A preparation method of a nitrogen and carbon doped bimetallic MOF-derived composite catalyst, characterized in that: It includes the following steps: Step 1: Dissolve Ni(NO3)2·6H2O and Co(NO3)2·6H2O in methanol and stir to form a metal salt solution. Dissolve 2-methylimidazole in methanol, quickly pour it into the metal salt solution, stir, then transfer it to a high-pressure reactor and react at 120 °C for 24 hours. Centrifuge, wash, and dry to obtain a bimetallic MOF precursor NiCo-MOF; Step 2: Pyrolyze at high temperature in an inert atmosphere (Ar / N2), control the temperature at 700 - 900 °C, with a heating rate of 2 - 5 °C / min, and hold for 2 - 4 hours; Step 3: Introduce SiO2 nanosphere templates as hard templates, remove the templates by etching with HF acid after carbonization to form a mesoporous-macroporous hierarchical structure; Step 4: Place the carbonized material and the phosphorus source sodium hypophosphite (NaH2PO2) at the upstream and downstream of a tubular furnace respectively, heat to 300 - 400 °C at a rate of 2 °C / min under an Ar atmosphere, and hold for 2 hours to form a CoP@NiP / NC composite structure. Step 5: Purify and wash with 0.5 M HCl or HNO3 acid for 1 - 2 hours to remove unreacted metal oxides, with a usage amount 10 - 20 times that of the catalyst, then use carbon cloth or nickel foam as the substrate, with a loading amount of 1 - 3 mg / cm² and an impregnation time of 12 - 24 hours, and a drying temperature of 80 - 150 °C.
2. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: In Step 1, the total metal ion concentration of nickel nitrate and cobalt nitrate is 0.05 - 0.2 mol / L, and the molar ratio of 2-methylimidazole to the metal salt is 4:
1.
3. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: In Step 2, the flow rate of the inert gas is 50 - 100 mL / min, and the nitrogen content of the carbon matrix after pyrolysis is 8 at%.
4. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: In Step 3, the mass ratio of the SiO2 nanosphere template to the MOF precursor is 1:10, and the etching time is 12 hours.
5. The preparation method of a nitrogen-carbon doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: In Step 4, the mass ratio of sodium hypophosphite to the carbonized material is 1:10 - 1:20, and the particle size of CoP@NiP particles after phosphidation is 5 ± 1 nm.
6. The preparation method of a nitrogen-carbon doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: In Step 5, the usage amount of the acid washing solution is 10 - 20 times the mass of the catalyst, and the impregnation time is 12 - 24 hours.
7. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, wherein: The nitrogen-doped carbon matrix is generated by the pyrolysis of 2-methylimidazole, and combined with the phosphidation treatment to form an N / P co-doped conductive network with a conductivity > 200 S / m.
8. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: The specific surface area of the hierarchical pore structure is 480 m² / g, the pore volume is 1.0 cm³ / g, and the proportion of mesopores is ≥70%. The catalyst can be compounded with a conductive substrate (nickel foam, carbon cloth), and the loading amount is 1-3 mg / cm 2 , and is used in industrial electrolyzers (production capacity ≥ 1 Nm 3 H2 / h).
9. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: The stability of the catalyst in an acidic environment (pH < 7) > 1000 hours (current retention rate > 95%), and the OER overpotential in a basic environment (pH > 7) ≤ 238 mV@10 mA / cm².
10. The preparation method of a nitrogen and carbon co-doped bimetallic MOF-derived composite catalyst according to claim 1, characterized in that: The catalyst is suitable for hydrogen production by electrolyzing water in the full pH range, including proton exchange membrane electrolyzers (acidic), alkaline electrolyzers, and neutral media (simulated seawater). The deactivated catalyst can be soaked in 0.5 M H2SO4 for 2 hours to remove surface oxides, and the activity recovery rate after regeneration > 90%. The preparation process of the catalyst uses a continuous tubular furnace for mass production, with a production capacity ≥ 100 kg / day.